Pharmacological safe dose assessment of Mangifera indica Linn. leaves extract according to the Organization for Economic Cooperation and Development (OECD) 420 standards: Pharmacological safe dose of Mangifera indica Linn. leaves extract (Indian Journal of Traditional Knowledge (IJTK), 2025)
Mangifera indica Linn. leaves extract owns various medicinal properties including antioxidant, anti-diabetic, anti-cancerous, and anti-inflammatory activities. The aim of this study is to find out the safe oral dose of ethanolic extract of M. indica leaves on Swiss albino mice for pharmacological purpose. The Organization for Economic Cooperation and Development (OECD) Guideline 420 was followed to assess the acute oral toxicity. M. indica leaf extract was administered in a dose dependent manner orally at dosages of 50-, 300-, and 2000- mg. kg-1 body weight (b.w.) in the sighting study, with one animal used for each dosage. Based on the sighting study, the highest dose of 2000 mg. kg-1 b.w. of M. indica leaves extract was selected for the main study. Continuous monitoring for successive 14 days was done for any behavioural sign of toxicity. Body weight and relative organ weight and biochemical parameters were assessed, and gross necropsy was performed on 15th day. Further, hematoxylin and eosin (H&E) staining of the liver, kidney and testes was performed. The body weight was significantly increased in both studies without any major changes in relative organ weight (ROW), and histology of H&E-stained tissues, wherein no obvious signs of toxicity and mortality were seen. The results of this study suggest that the M. indica leaves extract can be categorized as unclassified according to the Globally Harmonised Classification System for chemical substances and mixtures. Therefore, our study concludes that ethanolic extract of M. indica leaves less than 2000 mg. kg-1 b.w. can be considered safe for traditional therapeutic uses.